Unraveling thickness-dependent structural properties of CrSBr nanoflakes using hyperspectral TERS imaging - Danylo, Iryna; Mrđenović, Dušan; Bienz, Siiri; Zenobi, Renato; Sofer, Zdeněk; Kumar, Naresh; Veselý, Martin (Optics communications, 2025)
CrSBr, a layered van der Waals material with intrinsic air stability and layer-dependent magnetic and electronic properties, has emerged as a promising 2D semiconductor. However, nanoscale insight into its thickness-dependent structural and electronic behavior remains limited. In this study, we employ hyperspectral tip-enhanced Raman spectroscopy (TERS) imaging to investigate the vibrational and electronic properties of exfoliated CrSBr nanoflakes. Both confocal Raman and TERS measurements reveal a systematic enhancement of the A2g Raman mode relative to the A3g mode in thinner flakes. The I (A2g)/I (A3g) intensity ratio decreases consistently with increasing flake thickness, reflecting underlying changes in the electronic band structure. Hyperspectral TERS mapping confirms this trend at the single-flake level and suggests a resonance Raman enhancement influenced by electron–phonon coupling near the band edge. Our results establish the I (A2g)/I (A3g) ratio as a sensitive spectroscopic marker for thickness-dependent band structure evolution in CrSBr. More broadly, this work highlights hyperspectral TERS as a powerful tool for probing local structure–property relationships in emerging low-dimensional materials. [Display omitted]